The role of micro-influencers in social media marketing: A quantitative study on purchase intent using source credibility theory - Yosef Dema; Elisabeth Vita Mutiarawati; Yohanes Langgar Billy (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2025)
In the ever-evolving realm of digital marketing, this study delves into how micro-influencer credibility—conceptualized through the dimensions of expertise, trustworthiness, and attractiveness—shapes consumer purchase intent on social media platforms. Grounded in Source Credibility Theory, the research employs a quantitative design, gathering responses from 270 social media users via a structured online survey. Employing Structural Equation Modeling (SEM-PLS), the analysis uncovers that while trustworthiness and attractiveness significantly sway consumer behavior, expertise surprisingly falls short of exerting measurable impact. This departure from prior emphasis on knowledge-based persuasion suggests a shifting consumer landscape—where authenticity and visual appeal resonate more than authority. Even more striking is the discovery that variations in age, gender, and social media habits do not meaningfully moderate these relationships. This uniformity underscores a broad psychological consistency in how consumers evaluate influencers. Marketers and practitioners, therefore, are encouraged to recalibrate their strategies, prioritizing emotional resonance and personal branding over technical qualifications.